Characteristics and outcomes of atrial fibrillation detected before and after acute ischemic stroke - D'Anna, Lucio; Romoli, Michele; Harvey, Kirsten; Korompoki, Eleni; Veltkamp, Roland (Journal of neurology, 2024)
Background: Atrial fibrillation (AF) can be known before the stroke (KAF) or be newly detected after stroke (AFDAS). It is unknown whether the outcome of stroke differs between KAF and AFDAS. We performed a propensity-matched analysis to investigate the outcome of patients with AFDAS and their counterparts with KAF. Methods: We analysed a consecutive series of patients enrolled into the EIDASAF study, a single centre, retrospective study of ischemic stroke patients with a diagnosis of AF before or after the event who had been admitted to the Hyperacute Stroke Unit of Imperial College Healthcare NHS Trust between 2010 and 2017. Results: Overall, our cohort included 959 patients with AF and acute ischemic stroke. After propensity score matching, 547 patients were matched (404 KAF group and 143 AFDAS group). The rates of in hospital death and of haemorrhagic transformation were significantly higher in KAF patients compared to AFDAS patients. Logistic regression analysis did not reveal a statistically significant influence of AF subtypes on the outcome of death. However, in logistic regression analysis KAF was associated with increased probability of haemorrhagic transformation (OR 9.64; CI 1.29–71.68, p = 0.022) after the index event. Conclusion:KAF is associated with an increased risk of haemorrhagic transformation but not of death when compared to AFDAS.